POLA KONFLIK PARTAI PERSATUAN PEMBANGUNANDAN RELASI KONFLIKNYA DENGAN NEGARA DI ERA ORDE BARU DAN REFORMASI - Suswanto (FISIPOOL UMY, 2015)
This afticle is written to explain conflict pattem that faced by Paftai Persatuan Pembangunan ( PPP ) in the New Order Era and Reformation Era. The afticle is not only explain PPP'S conflict pattern but also explore relation between conflict and state. ln New Order Era, The politicat padies unification policy made internal conflict at political pafty. PPP was one of political pafties that tasting of intemal conflict in New Ordet Era. After New Order Era collapse, PPP stillfaced internal conflict. Some officials came out from PPe then they established new political pafty.